Method for testing anti-blue light effect of cosmetics
By applying cosmetic samples on the transparent body and performing anti-blue light detection, the blue light protection rate is calculated, and the problem of lack of quantitative and qualitative detection methods in the prior art is solved, and the accurate evaluation of the anti-blue light effect of cosmetics is achieved.
Patent Information
- Application Number
- CN202411369561.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art lacks quantitative and qualitative detection methods to evaluate the anti-blue light effect of cosmetics.
By coating the test sample on the transparent body, a film layer of 2-3 μm was formed, and anti-blue light detection was performed at a limited distance, and the blue light protection rate was calculated to achieve quantitative and qualitative detection.
This method can accurately detect the anti-blue light effect of cosmetics, is simple to operate, and can quantitatively analyze the anti-blue light effect.
Smart Images

Figure BDA0005067207470000081 
Figure HDA0005233743640000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of cosmetics, and more specifically, to a method for testing the anti-blue light effect of cosmetics. Background Art
[0002] Cosmetics products include foundation, pressed powder, rouge, eye shadow, eyelashes, eyebrow pencils, eyelid products, eye makeup removers, lip balm and other products.
[0003] Blue light refers to high-energy, high-frequency visible light with a wavelength of 380-500nm. It is commonly found in sunlight, computers, mobile phones, room LED lights, etc. It has high energy and strong penetrating power. It not only hurts the eyes, but also causes photoaging of the skin. In addition, blue light can reach the deep dermis of the skin, causing oxidative damage to cell DNA and accelerating skin aging. The blue light from electronic devices has a cumulative effect on the skin.
[0004] Therefore, anti-blue light products are gradually gaining attention, but there is currently a lack of quantitative and qualitative testing methods for the anti-blue light effects of cosmetics. Summary of the invention
[0005] In order to quantitatively and qualitatively detect the anti-blue light effect of cosmetics, the present application provides a method for testing the anti-blue light effect of cosmetics.
[0006] The present application provides a method for testing the anti-blue light effect of cosmetics, which adopts the following technical solution: A method for testing the anti-blue light effect of cosmetics, comprising the following steps: S1. Take 2-3 parts of the test sample by weight and place them on a transparent body. After fixing, apply the test sample on the transparent body through coating treatment to form a film of 2-3 μm to obtain a sample; S2. Subject the samples to anti-blue light testing, where the samples are 5-10 cm away from the blue light source, and a blank group is used as a control. The blue light protection rate is calculated to complete the anti-blue light effect test.
[0007] By adopting the above technical solution, after the sample is coated on the transparent body, a firm film layer is formed to obtain the sample. The sample is tested for anti-blue light and the distance from the blue light is limited to ensure the anti-blue light effect of the sample. The detection method is relatively accurate and simple to operate. At the same time, combined with the calculation of the blue light protection rate, it can quantitatively and qualitatively detect the anti-blue light effect.
[0008] Preferably, the test sample is any liquid product such as liquid foundation or sunscreen, and the transparent body is transparent cardboard.
[0009] By adopting the above technical solution, ordinary liquid powder liquid, sunscreen, etc. have a certain anti-blue light effect. Testing the anti-blue light effect on transparent cardboard can not only quantitatively and qualitatively detect the anti-blue light effect, but also the operation is relatively convenient.
[0010] Preferably, the test sample is composed of an emulsion and a base sample in a mass ratio of 1:0.1-0.12; the base sample contains one or more of hydrophobic titanium dioxide and iron oxide; and the transparent body is transparent cardboard.
[0011] By adopting the above technical scheme, since hydrophobic titanium dioxide and iron oxide are high refractive index materials, they can be directly mixed with the emulsion for anti-blue light effect testing; after the emulsion is evenly mixed with the hydrophobic titanium dioxide and iron oxide, the anti-blue light effect is tested through transparent cardboard, and the lipophilicity of the emulsion is utilized to facilitate the more uniform dispersion of the hydrophobic titanium dioxide and iron oxide in the emulsion. For raw materials that do not become transparent when dispersed in the emulsion, they are dispersed in the emulsion and then tested on transparent cardboard for the anti-blue light effect, and the blue light protection rate can be clearly observed and calculated, thereby achieving quantitative and qualitative analysis of the anti-blue light effect.
[0012] Preferably, the hydrophobic titanium dioxide is made of titanium dioxide particles, shellac liquid and hydroxyapatite whiskers in a mass ratio of 1:0.05-0.1:0.1-0.2.
[0013] By adopting the above technical scheme, the viscosity of shellac liquid is utilized to facilitate bonding hydroxyapatite whiskers to the surface of titanium dioxide particles. Shellac itself has the advantage of a low refractive index, and the network structure formed by hydroxyapatite whiskers on the surface of titanium dioxide particles further refracts ultraviolet rays, blue light, etc., thereby further improving the anti-blue light effect. The cosmetics prepared using the hydrophobic titanium dioxide have good anti-blue light effect, and can also assist in verifying the qualitative and quantitative analysis of the anti-blue light test method.
[0014] Preferably, the emulsion comprises the following raw materials in parts by weight: 2-3 parts of lauryl PEG-10 tri(trimethylsiloxy)silyl ethyl polymethicone, 0.8-1.5 parts of PEG-10 polydimethylsiloxane, 8-12 parts of cyclopentasiloxane, 3-5 parts of C12-15 alcohol benzoate, 3-5 parts of phenyl trimethicone, 4-6 parts of trimethylsiloxysilicate, 3.5-4 parts of diisostearyl malate, 0.3-0.8 parts of tocopheryl acetate, 98-104 parts of water, 3-8 parts of butylene glycol, 0.6-1.0 parts of magnesium sulfate, 0.3-0.6 parts of propylene glycol, 0.2-0.5 parts of phenoxyethanol, 0.3-0.6 parts of caprylyl glycol, 2-5 parts of acetyl glucosamine, and 2-5 parts of sodium stearoyl glutamate.
[0015] By adopting the above technical scheme, acetyl glucosamine and sodium stearoyl glutamate are combined, and the hydrophilic group in acetyl glucosamine is utilized to facilitate the connection of water and alcohol substances in the emulsion, and the connection effect of the lipophilic group in sodium stearoyl glutamate and the ester substances, as well as the connection effect of the hydrophilic group and acetyl glucosamine, it is convenient to form a structurally stable emulsion. When the emulsion is applied to the surface of transparent cardboard, it can be stably adhered, and the hydrophobic titanium dioxide and iron oxide can be evenly dispersed, thereby facilitating the qualitative and quantitative analysis of the anti-blue light effect of the sample.
[0016] Preferably, the coating process uses a 2-3 μm wire rod coater and uniformly coats at a sliding speed of 1-2 mm / s.
[0017] By adopting the above technical solution, the coating tool and the sliding speed are limited to ensure that the sample is evenly attached to the surface of the transparent body, thereby facilitating the qualitative and quantitative analysis of the anti-blue light effect of the sample.
[0018] Preferably, the test sample is a dry powder, which contains one or more of mica, silica, and alumina; and the transparent body is a long transparent tape.
[0019] Preferably, in S1, 0.15-0.2 parts of the sample by weight are placed on a long transparent adhesive tape, and after fixing, the sample is evenly spread on the tape to form a film of 2-3 μm to obtain a sample.
[0020] By adopting the above technical scheme, since raw materials such as mica, silica, and alumina have a low refractive index and are easy to become transparent when dispersed in an emulsion, the dry powder is combined with a long transparent tape, and the adhesive effect of the long transparent tape is utilized to adhere the dry powder to the surface of the long transparent tape for anti-blue light detection and analysis. The shielding effect of the substances in the dry powder on blue light is analyzed, and combined with the anti-blue light effect detection method, quantitative and qualitative detection of the anti-blue light effect of cosmetics can be achieved.
[0021] Preferably, the anti-blue light detection comprises the following steps: Fix the blue light source, fix the sample 5-7cm in front of the light source, fix the black light screen 20-22cm in front of the light source, turn off the power of the room, turn on the blue light source, and test the blue light transmittance.
[0022] By adopting the above technical solution, the blue light source is fixed and then irradiated to the sample, so that the blue light source can reach the sample surface evenly, and the distance between the sample and the light source is limited to ensure that the wavelength of the blue light reaches the sample surface, thereby realizing the detection of the anti-blue light effect, and limiting the distance between the black light screen and the light source to further ensure the detection of the anti-blue light effect, which is not easily affected by other light sources, thereby facilitating the quantitative and qualitative detection of the anti-blue light effect of cosmetics, and the operation steps are relatively convenient.
[0023] Preferably, the anti-blue light detection comprises the following steps: A black box was made with holes at both ends, which were coaxially arranged. A xenon lamp was placed in one hole as the light source, and a handheld UV spectrometer was placed in the other hole. The test sample was placed 8-10 cm away from the light source. After the xenon lamp was preheated for 28-32 minutes, the light was turned on to test the blue light transmittance of the sample, and the irradiance in the UV zone was recorded at the same time, and the UV protection rate was calculated.
[0024] By adopting the above technical solution, the black box openings are coaxially set, one hole is for light source, and the other hole is for ultraviolet detection. Combined with the limited light source distance, it is ensured that ultraviolet light and blue light reach the sample surface, and the anti-blue light effect analysis is achieved. Combined with the ultraviolet protection rate and blue light protection rate, it is possible to verify the anti-blue light effect of cosmetics and conduct quantitative and qualitative detection.
[0025] In summary, this application has the following beneficial effects: 1. After the sample is coated on the transparent body, a firm film layer is formed to obtain the sample. The sample is tested for anti-blue light and the distance from the blue light is limited to ensure the anti-blue light effect of the sample. The detection method is relatively accurate and simple to operate. At the same time, combined with the calculation of the blue light protection rate, it can quantitatively and qualitatively detect the anti-blue light effect.
[0026] 2. After the emulsion is evenly mixed with hydrophobic titanium dioxide and iron oxide, the anti-blue light effect is tested through transparent cardboard. The lipophilicity of the emulsion is used to facilitate the more uniform dispersion of hydrophobic titanium dioxide and iron oxide in the emulsion. For raw materials that do not become transparent when dispersed in the emulsion, they are dispersed in the emulsion and then tested on transparent cardboard for anti-blue light effect. The blue light protection rate can be clearly observed and calculated, thereby achieving quantitative and qualitative analysis of the anti-blue light effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the anti-blue light effect diagram of the blank control group, Example 1, and Example 4 of the present application. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with embodiments.
[0029] Preparation Example of Hydrophobic Titanium Dioxide The following raw materials are all commercially available.
[0030] Preparation Example 1: Hydrophobic titanium dioxide was prepared by the following method: 0.08 kg of shellac liquid is evenly sprayed on the surface of 1 kg of titanium dioxide particles, and then 0.17 kg of hydroxyapatite whiskers are added. The average particle size of the titanium dioxide particles is 3 μm, the shellac liquid is a shellac ethanol solution with a mass fraction of 1%, the average length of the hydroxyapatite whiskers is 200 μm, and the addition rate of the hydroxyapatite whiskers is 60 g / min. During the addition process, the titanium dioxide particles are stirred at a speed of 120 r / min. After being evenly mixed, the titanium dioxide particles are dispersed until they do not stick to each other and agglomerate to obtain a finished product.
[0031] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 0.05 kg of shellac liquid is evenly sprayed on the surface of 1 kg of titanium dioxide particles, and then 0.1 kg of hydroxyapatite whiskers are added. The average particle size of the titanium dioxide particles is 3 μm, the shellac liquid is a shellac ethanol solution with a mass fraction of 1%, the average length of the hydroxyapatite whiskers is 200 μm, and the addition rate of the hydroxyapatite whiskers is 60 g / min. During the addition process, the titanium dioxide particles are stirred at a speed of 120 r / min. After being evenly mixed, the titanium dioxide particles are dispersed until they do not stick to each other and agglomerate to obtain a finished product.
[0032] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 0.1 kg of shellac liquid is evenly sprayed on the surface of 1 kg of titanium dioxide particles, and then 0.2 kg of hydroxyapatite whiskers are added. The average particle size of the titanium dioxide particles is 3 μm, the shellac liquid is a shellac ethanol solution with a mass fraction of 1%, the average length of the hydroxyapatite whiskers is 200 μm, and the addition rate of the hydroxyapatite whiskers is 60 g / min. During the addition process, the titanium dioxide particles are stirred at a speed of 120 r / min. After being evenly mixed, the titanium dioxide particles are dispersed until they do not stick to each other and agglomerate to obtain a finished product.
[0033] Example of emulsion preparation Among the following raw materials, lauryl PEG-10 tri(trimethylsiloxy)silylethyl polymethicone was purchased from Aocui Technology Co., Ltd.; other raw materials are commonly available on the market.
[0034] Preparation Example 4: The emulsion was prepared by the following method: 2.5kg of lauryl PEG-10 tri(trimethylsiloxy)silyl ethyl polymethicone, 1kg of PEG-10 polydimethylsiloxane, 10kg of cyclopentasiloxane, 4kg of C12-15 alcohol benzoate, 4kg of phenyl trimethicone, 5kg of trimethylsiloxysilicate, 3.6kg of diisostearyl malate, 0.5kg of tocopheryl acetate, 100kg of water, 6kg of butylene glycol, 0.9kg of magnesium sulfate, 0.5kg of propylene glycol, 0.4kg of phenoxyethanol, 0.4kg of caprylyl glycol, 3.5kg of acetyl glucosamine, 3.5kg of sodium stearoyl glutamate; The preparation method is as follows: Lauryl PEG-10 tri(trimethylsiloxy)silylethyl polymethicone, PEG-10 polydimethylsiloxane, cyclopentasiloxane, C12-15 alcohol benzoate, phenyl trimethicone, trimethylsiloxysilicate, diisostearyl malate, and tocopherol acetate are mixed, added into a beaker, and stirred and dispersed evenly to obtain a phase A mixture; water, butylene glycol, magnesium sulfate, propylene glycol, phenoxyethanol, caprylyl glycol, acetyl glucosamine, and sodium stearoyl glutamate are mixed to obtain a phase B mixture; Add the phase B mixture to the phase A mixture, homogenize at 5000 rpm for 3 min, and discharge to obtain an emulsion.
[0035] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 2kg of lauryl PEG-10 tri(trimethylsiloxy)silyl ethyl polymethicone, 0.8kg of PEG-10 polydimethylsiloxane, 8kg of cyclopentasiloxane, 3kg of C12-15 alcohol benzoate, 3kg of phenyl trimethicone, 4kg of trimethylsiloxysilicate, 3.5kg of diisostearyl malate, 0.3kg of tocopheryl acetate, 98kg of water, 3kg of butylene glycol, 0.6kg of magnesium sulfate, 0.3kg of propylene glycol, 0.2kg of phenoxyethanol, 0.3kg of caprylyl glycol, 2kg of acetyl glucosamine, and 2kg of sodium stearoyl glutamate.
[0036] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 3kg of lauryl PEG-10 tri(trimethylsiloxy)silyl ethyl polymethicone, 1.5kg of PEG-10 polydimethylsiloxane, 12kg of cyclopentasiloxane, 5kg of C12-15 alcohol benzoate, 5kg of phenyl trimethicone, 6kg of trimethylsiloxysilicate, 4kg of diisostearyl malate, 0.8kg of tocopheryl acetate, 104kg of water, 8kg of butylene glycol, 1kg of magnesium sulfate, 0.6kg of propylene glycol, 0.5kg of phenoxyethanol, 0.6kg of caprylyl glycol, 5kg of acetyl glucosamine, and 5kg of sodium stearoyl glutamate. Example
[0037] The following items are all commercially available.
[0038] Embodiment 1: A method for testing the anti-blue light effect of cosmetics: S1. Place a transparent card on a flat plate, then weigh 2 g of the test sample and place it on the front end of the transparent card, and fix it with a vacuum machine, then use a 2 μm wire rod coater to slide on the test sample at a uniform speed of 1 mm / s. After the coating is completed, a uniform 2 μm film is formed to obtain a sample; the test sample is a liquid foundation, and the liquid foundation is Lancome long-lasting liquid foundation; the transparent card is a transparent body; S2. Fix the blue light source at the front end, fix the sample 5 cm in front of the light source, and fix the black light screen 20 cm in front of the light source. Then turn off the room light source to reduce the interference of ambient light, turn on the blue light source, test the blue light transmittance of the sample on the transparent plate, and make a blank control group for the blue light transmittance of the transparent plate without sample. By comparing the photos, the blue light transmittance can be judged, and the anti-blue light effect can be qualitatively judged. At the same time, the pictures are analyzed and processed by ImageJ to test the blue light intensity of the pictures. The blank group intensity is recorded as I0, and the sample experimental group is recorded as I1. Each data is measured three times and the average value is taken. The blue light protection rate % = (I0-I1) / I0×100%, and the anti-blue light effect detection is completed.
[0039] Embodiment 2: This embodiment differs from Embodiment 1 in that: S1. Place a transparent plate on a flat plate, then weigh 3g of the test sample and place it on the front section of the transparent cardboard, and fix it with a vacuum machine, then use a 2μm wire rod coater to slide on the test sample at a uniform speed of 2mm / s. After the coating is completed, a uniform 3μm film is formed to obtain a sample; the test sample is liquid foundation, and the transparent cardboard is a transparent body; S2. Fix the blue light source at the front end, fix the sample 7 cm in front of the light source, and fix the black light screen 22 cm in front of the light source. Then turn off the room light source to reduce the interference of ambient light, turn on the blue light source, test the blue light transmittance of the sample on the transparent plate, and make a blank control group for the blue light transmittance of the transparent plate without sample. By comparing the photos, the blue light transmittance can be judged, and the anti-blue light effect can be qualitatively judged. At the same time, the pictures are analyzed and processed by ImageJ to test the blue light intensity of the pictures. The blank group intensity is recorded as I0, and the sample experimental group is recorded as I1. Each data is measured three times and the average value is taken. The blue light protection rate % = (I0-I1) / I0×100%, and the anti-blue light effect detection is completed.
[0040] Embodiment 3: A method for testing the anti-blue light effect of cosmetics: S1. Weigh 2 g of the emulsion prepared in Preparation Example 4 and 0.2 g of the basic sample, which is commercially available hydrophobic titanium dioxide, and mix and stir them to obtain a test sample; apply the mixture to the front end of a transparent cardboard and fix it with a vacuum machine, and then use a 2 μm wire rod coater to slide on the test sample at a uniform speed of 1 mm / s. After the coating is completed, a uniform 2 μm film is formed to obtain a sample; the transparent cardboard is a transparent body; S2. Make a small black box with a hole at each end. The two holes are coaxially arranged on a horizontal line. A xenon lamp is placed in one hole as the light source, and the photosensitive probe of a handheld ultraviolet spectrometer is placed in the other hole. A slot is left in the middle to place the test sample. The test sample is 10 cm away from the light source. The xenon lamp is turned on and preheated for half an hour. The ultraviolet irradiance IrUv1, the blue light irradiance IrBlue1 and the spectrum curve of the test sample are tested. A blank transparent plate is used as a blank control group to record the ultraviolet irradiance IrUv0, the blue light irradiance IrBlue0 and the spectrum curve. Each data is measured 3 times and the average value is taken. The ultraviolet protection rate % = (IrUv0-IrUv1) / IrUv0×100%; the blue light protection rate % = (IrBlue0-IrBlue1) / IrBlue0×100%.
[0041] Embodiment 4: This embodiment differs from Embodiment 3 in that: S1. Weigh 2 g of the emulsion prepared in Preparation Example 4 and 0.2 g of the basic sample, wherein the basic sample is the hydrophobic titanium dioxide prepared in Preparation Example 1, and mix and stir them evenly to obtain a test sample; the mixture is coated on the front end of a transparent cardboard and fixed with a vacuum machine, and then a 2 μm wire rod coater is used to slide uniformly on the test sample at a speed of 1 mm / s. After the coating is completed, a uniform 2 μm film is formed to obtain a sample; the transparent cardboard is a transparent body; S2. Make a small black box with a hole at each end. The two holes are coaxially arranged on a horizontal line. A xenon lamp is placed in one hole as the light source, and the photosensitive probe of a handheld ultraviolet spectrometer is placed in the other hole. A slot is left in the middle to place the test sample. The test sample is 10 cm away from the light source. The xenon lamp is turned on and preheated for half an hour. The ultraviolet irradiance IrUv1, the blue light irradiance IrBlue1 and the spectrum curve of the test sample are tested. A blank transparent plate is used as a blank control group to record the ultraviolet irradiance IrUv0, the blue light irradiance IrBlue0 and the spectrum curve. Each data is measured 3 times and the average value is taken. The ultraviolet protection rate % = (IrUv0-IrUv1) / IrUv0×100%; the blue light protection rate % = (IrBlue0-IrBlue1) / IrBlue0×100%.
[0042] Embodiment 5: This embodiment differs from Embodiment 4 in that: S1. Weigh 2 g of the emulsion prepared in Preparation Example 5 and 0.2 g of a basic sample, where the basic sample is the hydrophobic titanium dioxide prepared in Preparation Example 2, and mix and stir them evenly to obtain a test sample.
[0043] Embodiment 6: This embodiment differs from Embodiment 4 in that: S1. Weigh 2 g of the emulsion prepared in Preparation Example 6 and 0.2 g of a basic sample, where the basic sample is the hydrophobic titanium dioxide prepared in Preparation Example 3, and mix and stir them evenly to obtain a test sample.
[0044] Embodiment 7: This embodiment differs from Embodiment 4 in that: No acetyl glucosamine and sodium stearoyl glutamate are added to the emulsion raw materials.
[0045] Embodiment 8: A method for testing the anti-blue light effect of cosmetics: S1. Cut a 10 cm long transparent tape and fix it on the frame. Weigh 0.15 g of the test sample and evenly apply it on the long transparent tape to obtain a sample. The test sample is mica and the long transparent tape is a transparent body. S2. Make a small black box with a hole at each end. The two holes are coaxially arranged on a horizontal line. A xenon lamp is placed in one hole as the light source, and the photosensitive probe of a handheld ultraviolet spectrometer is placed in the other hole. A slot is left in the middle to place the test sample. The test sample is 10 cm away from the light source. The xenon lamp is turned on and preheated for half an hour. The ultraviolet irradiance IrUv1, the blue light irradiance IrBlue1 and the spectrum curve of the test sample are tested. A blank transparent plate is used as a blank control group to record the ultraviolet irradiance IrUv0, the blue light irradiance IrBlue0 and the spectrum curve. Each data is measured 3 times and the average value is taken. The ultraviolet protection rate % = (IrUv0-IrUv1) / IrUv0×100%; the blue light protection rate % = (IrBlue0-IrBlue1) / IrBlue0×100%.
[0046] Embodiment 9: This embodiment differs from Embodiment 8 in that: S1. Cut a 10 cm long transparent tape and fix it on the frame. Weigh 0.2 g of the test sample and evenly apply it on the long transparent tape to obtain a sample. The test sample is aluminum oxide and the long transparent tape is a transparent body. S2. Make a small black box with a hole at each end. The two holes are coaxially arranged on a horizontal line. A xenon lamp is placed in one hole as the light source, and the photosensitive probe of a handheld ultraviolet spectrometer is placed in the other hole. A slot is left in the middle to place the test sample. The test sample is 10 cm away from the light source. The xenon lamp is turned on and preheated for half an hour. The ultraviolet irradiance IrUv1, the blue light irradiance IrBlue1 and the spectrum curve of the test sample are tested. A blank transparent plate is used as a blank control group to record the ultraviolet irradiance IrUv0, the blue light irradiance IrBlue0 and the spectrum curve. Each data is measured 3 times and the average value is taken. The ultraviolet protection rate % = (IrUv0-IrUv1) / IrUv0×100%; the blue light protection rate % = (IrBlue0-IrBlue1) / IrBlue0×100%.
[0047] Embodiment 10: A method for testing the anti-blue light effect of cosmetics: The test sample in S1 was titanium dioxide dry powder; S2. The samples were tested for anti-blue light using a UV-visible spectrometer, where the samples were 10 cm away from the blue light source, and the blank group was used as a control. The light absorption or transmittance curve of the test material was tested, and the blue light protection rate was calculated.
[0048] Performance testing 1. Blue light protection rate detection The anti-blue light effect was tested using the methods of Examples 1-10, and the light intensity and blue light protection rate were recorded.
[0049] 2. UV protection rate detection The anti-blue light effect was tested by the methods of Examples 1-10 respectively, and the ultraviolet irradiance and ultraviolet protection rate were recorded.
[0050] Table 1 Performance test table Combined with Examples 1-2 and the blank control group and Table 1, Figure 1 It can be seen that the liquid foundation has anti-blue light and anti-UV effects, and after analysis using anti-blue light methods, the anti-blue light effect can be quantitatively and qualitatively determined.
[0051] Combined with Example 3 and Example 4-6 and Table 1, Figure 1 It can be seen that the anti-blue light and anti-ultraviolet effects of the commercially available hydrophobic titanium dioxide are inferior to those prepared in the preparation example, which can not only reflect the anti-blue light effect of cosmetic raw materials, but also verify the qualitative and quantitative effects of the anti-blue light detection method.
[0052] It can be seen from Example 4 and Example 7 and Table 1 that the combination of acetyl glucosamine and sodium stearoyl glutamate in the emulsion can further improve the adhesion stability of the emulsion carrying hydrophobic titanium dioxide, thereby ensuring a uniform anti-blue light effect, and can also qualitatively and quantitatively verify the anti-blue light effect.
[0053] It can be seen from Examples 8-9 and Table 1 that the dry powder, as a raw material for cosmetics, has a certain anti-blue light effect, and the anti-blue light effect can be qualitatively and quantitatively verified.
[0054] It can be seen from Example 10 and Table 1 that an ordinary UV-visible spectrometer can also detect the blue light resistance of a substance.
[0055] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for testing the anti-blue light effect of cosmetics, characterized in that: The steps include: S1. Take 2-3 parts of the test sample by weight and place them on a transparent body. After fixing, apply the test sample on the transparent body through coating treatment to form a film of 2-3 μm to obtain a sample; S2. Subject the samples to anti-blue light testing, where the samples are 5-10 cm away from the blue light source, and a blank group is used as a control. The blue light protection rate is calculated to complete the anti-blue light effect test.
2. The method for testing the anti-blue light effect of cosmetics according to claim 1, characterized in that: The test sample is any liquid product such as liquid foundation and sunscreen, and the transparent body is transparent cardboard.
3. The method for testing the anti-blue light effect of cosmetics according to claim 1, characterized in that: The test sample is composed of an emulsion and a base sample in a mass ratio of 1:0.1-0.12; the base sample contains one or more of hydrophobic titanium dioxide and iron oxide; and the transparent body is transparent cardboard.
4. A method for testing the anti-blue light effect of cosmetics according to claim 3, characterized in that: The hydrophobic titanium dioxide is made of titanium dioxide particles, shellac liquid and hydroxyapatite whiskers in a mass ratio of 1:0.05-0.1:0.1-0.
2.
5. The method for testing the anti-blue light effect of cosmetics according to claim 3, characterized in that: The emulsion comprises the following raw materials in parts by weight: 2-3 parts of lauryl PEG-10 tri(trimethylsiloxy)silyl ethyl polymethicone, 0.8-1.5 parts of PEG-10 polydimethylsiloxane, 8-12 parts of cyclopentasiloxane, 3-5 parts of C12-15 alcohol benzoate, 3-5 parts of phenyl trimethicone, 4-6 parts of trimethylsiloxysilicate, 3.5-4 parts of diisostearyl malate, 0.3-0.8 parts of tocopheryl acetate, 98-104 parts of water, 3-8 parts of butylene glycol, 0.6-1.0 parts of magnesium sulfate, 0.3-0.6 parts of propylene glycol, 0.2-0.5 parts of phenoxyethanol, 0.3-0.6 parts of caprylyl glycol, 2-5 parts of acetyl glucosamine, and 2-5 parts of sodium stearoyl glutamate.
6. The method for testing the anti-blue light effect of cosmetics according to claim 1, characterized in that: The coating process uses a 2-3 μm wire rod coater and uniformly coats at a sliding speed of 1-2 mm / s.
7. The method for testing the anti-blue light effect of cosmetics according to claim 1, characterized in that: The test sample is a dry powder, which contains one or more of mica, silica, and alumina; and the transparent body is a long transparent tape.
8. The method for testing the anti-blue light effect of cosmetics according to claim 7, characterized in that: S1, taking 0.15-0.2 parts of the sample by weight and placing it on a long transparent adhesive tape, after fixing, evenly smearing the sample on the tape to form a film of 2-3 μm to obtain the sample.
9. The method for testing the anti-blue light effect of cosmetics according to claim 1, characterized in that: The anti-blue light detection comprises the following steps: Fix the blue light source, fix the sample 5-7cm in front of the light source, fix the black light screen 20-22cm in front of the light source, turn off the power of the room, turn on the blue light source, and test the blue light transmittance.
10. The method for testing the anti-blue light effect of cosmetics according to claim 1, characterized in that: The anti-blue light detection comprises the following steps: A black box was made with holes at both ends, which were coaxially arranged. A xenon lamp was placed in one hole as the light source, and a handheld UV spectrometer was placed in the other hole. The test sample was placed 8-10 cm away from the light source. After the xenon lamp was preheated for 28-32 minutes, the light was turned on to test the blue light transmittance of the sample, and the irradiance in the UV zone was recorded at the same time, and the UV protection rate was calculated.